Research skills for policy and development how to find out fast / edited by Alan Thomas and Giles Mohan. - Thomas, Alan 1948-; Mohan, Giles 1966- (Sage Publications, 2007)
Unlike a simple h̀ow to' guide, Research Skills for Policy and Development provides a critique of various methods and situates these approaches within r̀eal life' organisational settings, enabling those working in or studying development to locate, evaluate and use relevant information quickly but rigorously. The successor to Finding Out Fast (SAGE, 1998) it reflects the changes in development management theories and practice over the last seven years, and includes new material and advice on critical use of the web as a resource and research tool.